ANALISIS MODEL KOMUNIKASI PEMASARAN TERPADU ‎ ‎(INTEGRATED MARKETING COMMUNICATION) ‎ UMRAH AL BAHJAH TOUR & TRAVEL CIREBON - desy salma aeni (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2022)
This study, raising a problem, namely the Analysis of the Integrated Marketing Communication Model for Umrah Al Bahjah Tour & Travel Cirebon which is an important point in carrying out integrated marketing communications. Because, the very competitive competition in the tourism industry, namely the tour & travel business, must increase product advantages, excellent service and must also be able to promote these advantages by means of proper marketing communication. The challenges of tour & travel companies, especially Umrah, are getting more severe, namely the rapid development of information technology in the community. Umrah bureau actors must be ready to face it.The purpose of this study was to determine the effectiveness of the Integrated Marketing Communication Model for Umrah Al Bahjah Tour & Travel Cirebon. This study aims to describe and analyze the relevance between strategy and implementation of the Integrated Marketing Communication Model for Umrah Al Bahjah Tour & Travel Cirebon. Using theories relevant to the research theme, namely Communication Theory, Tour & Travel Business Theory, Business Communication Theory, Marketing Communication Theory, Marketing Communication Mix Theory, Integrated Marketing Communication Theory, Marketing Theory Sharia Principled Umrah Products. This study uses a qualitative approach with descriptive methods and phenomenological paradigms. Located at the head office of Albahjah Tour & Travel Cirebon.In this study, the focus taken is the Promotion aspect where the strategy currently being applied is the Integrated Marketing Communication strategy. Formulating an Integrated Marketing Communication strategy for a tour & travel company must be adjusted to the vision & mission, segmentation, targeting, and positioning of the company itself.The results of this study are: 1) Efectivity of the Integrated Marketing Communication Model for Umrah Al Bahjah Tour & Travel Cirebon. 2) There is an integration between strategy and implementation of Integrated Marketing Communication in marketing its Umrah products. 3) It is necessary to increase marketing through digital media such as Instagram, Facebook, websites, even in the future so that they can join e-commerce in order to reach a wider market.